The Asian shadow play - Tilakasiri, J. (Ratmalana : Sarvodaya Vishva Lekha, 1999)
Comprehensive study of shadow puppetry in several Asian countries.
Includes bibliographical references (p. 247-251) and index.
Keywords: Puppet theater -- Asia; Shadow puppets -- Asia; Shadow shows -- Asia